EFFECT OF PERCEIVED EASE OF USE AND SECURITY OF E-BANKING ON CUSTOMER SATISFACTION - Ngozi Folashade Diokpa (International Studies Journal)
E-Banking has transformed the banking industry in Nigeria with several new products and ways of conducting the banking business. This has led to increase competition in the banking sector and also to need to better satisfy bank customers. Therefore, there is a need to explore options that can improve customer satisfaction. The aim of this study is to examine the effect of perceived ease of use and security of e-banking on customers' satisfaction in Abuja. The data of this study was collected from primary source using questionnaire to obtain responses frombank customers. The collected data was the analyzed using correlation and regression analysiswith the SPSS version 20. Consequently, the findings from the study showed that perceived ease of use and security positively and significantly influence customers satisfaction of first bank customers in Abuja. The correlation analysis showed that there is a significant and positive relationship between E-banking attributes and customer satisfaction. Therefore, the study recommends that banks should improve the user friendliness of their e-banking channels and increase the level of encryption of their security to improve customers experience and increase satisfaction.